2021
DOI: 10.21608/ejhm.2021.175173
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Quality of Life after Laparoscopic Cholecystectomy

Abstract: Background: Laparoscopic Cholecystectomy is one of the most common surgical procedures. Quality of life (QOL) is a concept reflecting physical, social, and emotional attitudes. Surgical operation, as a traumatic treatment procedure, could affect QOL of the patients as well as treating them. Therefore, surgeons should try their best to improve patient's QOL in addition to focus on the more traditional outcomes of mortality, morbidity, and laboratory findings. Objectives: The aims of the current work were to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Our review of Saudi Arabian data revealed a need for more comprehensive and localized research on LC's cost-effectiveness. While early laparoscopic cholecystectomy appears to be more cost-effective than delayed laparoscopic cholecystectomy in high-income countries, there is a gap in the literature regarding other economies, including Saudi Arabia [ 9 ]. Such research could provide valuable insights for health policy and planning and management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review of Saudi Arabian data revealed a need for more comprehensive and localized research on LC's cost-effectiveness. While early laparoscopic cholecystectomy appears to be more cost-effective than delayed laparoscopic cholecystectomy in high-income countries, there is a gap in the literature regarding other economies, including Saudi Arabia [ 9 ]. Such research could provide valuable insights for health policy and planning and management.…”
Section: Discussionmentioning
confidence: 99%
“…While its definition might remain broad, encompassing physical, emotional, and social dimensions, its relevance has surged, especially when assessing medical interventions [ 8 ]. The outcomes as reported by patients, including pain and quality of life (QoL), become pivotal for a surgeon when considering a procedure [ 9 ]. Notably, the gastrointestinal quality of life index (GIQLI) is frequently employed to measure QoL for biliary tract diseases, indicating an improvement in gastrointestinal symptoms post-LC [ 10 ].…”
Section: Introductionmentioning
confidence: 99%